Nilai Moralitas dalam Sistem Syura (Suatu Model Sistem Politik Berdasarkan Hadis) - Muhamad Nasir (Al-Ulum, 2018)
This article examines the political system ever undertaken by the Prophet Muhammad especially when he was in Medina. The study finds out that the hadith texts show that the political practices of the Prophet indicated that he not only became the spiritual leader of the Muslims community, but also the leader of the state who made the syûrâ as a system in determining the direction of the government of Madinah. The syûrâ system not only offers a political system but also becomes the basis of ethics in politics so that politicians can improvise in exercising power without violating Islamic ethics. Islam does not set certain systems to be embraced by a predominantly Muslim country, although the term syûrâ is contained in the Qur'an and Hadith, but the most important thing is the substance of the syûrâ that should be the system for every country, especially in Indonesia.